Mimořádné události a informování obyvatelstva. - Austová, Kamila (Vysoké učení technické v Brně. Fakulta chemická, 2010)
Tato práce se zabývá mimořádnými událostmi a informováním obyvatelstva. V první části je popsáno rozdělení mimořádných událostí a informování obyvatelstva v jednotlivých fázích mimořádné události. Dále popisuje informovanost občana a jeho připravenost k sebeochraně. Zabývá se také tísňovými informačními rozhlasovými relacemi a Koncepcí ochrany obyvatelstva. Součástí práce jsou vlastní postřehy a návrhy k informování obyvatelstva.

This bachelor’s thesis is concerned with extraordinary events and providing information to the population. The first part describes the division of extraordinary events and providing information to the population in each phases of extraordinary events. In further describes the informedness of citizen and the preparedness for protecting itself of citizen. The work includes radio broadcast emergency information and evaluates the Conception of civil protection. Part of the work are my suggestions to providing information to the population.
Emergency Situations and Information of Population
Keywords: mimořádná událost; informování obyvatelstva; ochrana obyvatelstva; tísňové informace; sebeochrana občana; preventivně výchovná činnost; varování a vyrozumění obyvatelstva; extraordinary event; providing information to the population; civil protection; emergency information; protecting itself of citizen; preventive educational activity; warning and notification of the population